Opportunities and Challenges that Class Agreements Bring to Lowering Fifth Graders’ Disruptive Behavior (2023)
ABSTRACT : This action research aimed at identifying the opportunities and challenges on classroom agreements that may be implemented to diminish students’ disruptive behavior in class and improving their behavioral engagement. It was conducted in a public school in Rionegro, Antioquia with 26 fifth graders. Action strategies included involvement of students in the creation of classroom agreements which helped them reflect about their own behavior in class. Data gathering instruments included teacher’s journal, students’ reflections, and a focus group. Findings referred to the opportunity of how classroom agreements helped some students become aware of their own behavior to self-regulate and encourage other classmates to regulate themselves, and the challenge of how recognizing classroom agreements represented an issue for some students who continued misbehaving and self-regulated was perceived only after receiving a reward.